The Effect of Students’ Metacognitive Awareness and Reading Comprehension in Narrative Text of Second-Grade Students - Sianturi Febiyola Sianturi, Wina; Sinaga, Nenni Triana; Sidabutar, Usman (LPPPI Publishing, 2024)
This research aims to determine students’ metacognitive and reading comprehension in narrative text. This study investigates whether metacognitive awareness affects students' reading comprehension of narrative text at SMA N 3 Binjai. This research applied a quantitative approach, the population was the second-grade students at SMA N 3 Binjai in the 2024 academic year, and the sample was XI MIA 1 and XI MIA 2. The first sample involves 34 students for the experimental group (XI MIA 1) and the second sample involves 36 students for the control group (XI MIA 2). The instruments for collecting data were tests and questionnaires. There were pre-tests and post-tests for collecting data and the researcher gave pre-tests and post-tests to both classes. Based on the data, it was found that the result of the t-test (t-calculated) was higher than the t-table value at a significance level of p = 0,05 (2,1 > 1,995). Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This indicates that metacognitive awareness was significantly influence the reading comprehension achievement of second-grade students at SMA N 3 Binjai.